Breast cancer cell-induced platelet activation is compounded by tamoxifen and anastrozole in vitro. Issue 177 (May 2019) - Pather, K.; Dix-Peek, T.; Duarte, R.; Chetty, N.; Augustine, T.N.
Abstract: Platelet-tumour cell interaction is implicated in the initiation of breast cancer-associated thrombosis, with hormone-therapy (Tamoxifen/Anastrozole), increasing this risk. However, recent in vitro research indicates that Tamoxifen inhibits platelet activation, while the effects of Anastrozole on platelet activation are not well characterised. This study investigated platelet activation caused by Tamoxifen or Anastrozole-treated breast cancer cells in vitro . MCF7 and T47D cells were pre-treated with Tamoxifen or Anastrozole to mimic the effects of the drugs in vivo, and co-cultured with whole blood. Platelet activation was determined using flow cytometry. Platelet (CD41a + CD62P + ) was determined using an interval gating strategy. Platelet morphology was visualised using scanning electron microscopy. Our results support clinical findings, showing that hormone-therapy is associated with platelet activation. Tamoxifen-treated MCF7 cells increased P-selectin expression, with ultrastructural analysis showing fully spread platelets. Conversely, Tamoxifen-treated T47D cells decreased P-selectin expression with platelets showing signs of early aggregation. Anastrozole pre-treatment decreased P-selectin expression, with treated MCF7 cells inducing platelet membrane folds and lamellipodia extension, and treated T47D cells inducing platelet aggregation and fibrin network formation indicating hypercoagulation. The findings support clinical studies. Hormone-therapy augments tumour cell-induced platelet activation, which may be linked to cell phenotype. This may have clinical implications for treatment strategies. Highlights: Breast cancer cells induce heightened P-selectin expression dependent on phenotype. Hormone-therapy augments tumour cell-induced platelet activation. Tamoxifen-induced platelet activation in vitro is controversial and method based. Provides in vitro evidence for thrombotic effects of Anastrozole, data is lacking. Tamoxifen pre-treatment induced lamellipodia and filipodia extension of platelets. Anastrozole-treated T47D cells induced fibrin network formation in whole blood.